Trend Extraction From Time Series With Missing Observations - Ekkehart Schlicht (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2007)
Trend extraction from time series is often performed by using the filter proposed by Leser (1961), also known as the Hodrick-Prescott filter. A practical problem arises, however, when some data points are missing. This note proposes a method for coping with this problem.
urn:nbn:de:bvb:19-epub-1927-0
Keywords: C22; C32; C63; C14; 330; Trend extraction; missing observations; gaps; Hodrick-Prescott filter; Leser filter; spline; time-series; smoothing; interpolation.; Trend; Zeitreihenanalyse; Statistische Methodenlehre